An Approach to Supervision for Doctoral and Entry-Level Group Counseling Students. - Walsh, Robyn; Bambacus, Elizabeth; Gibson, Donna (Journal for Specialists in Group Work, 2017)
The purpose of this article is to provide a supervision approach to experiential groups that replaces professors with doctoral students in the chain of supervision, enlists a faculty member to provide supervision of supervision to the doctoral students, and translates supervision theory to meet the unique needs of group counseling supervision. This approach begins with an explanation of experiential training groups and reasons for group supervision, continues with a discussion of adapting supervision models for group supervision, and concludes with reflections and the authors’ recommendations for programs trying to navigate group counseling supervision issues.